2021
DOI: 10.1101/2021.06.08.447513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HSV-1 ICP22 is a selective viral repressor of cellular RNA polymerase II-mediated transcription elongation

Abstract: The Herpes Simplex Virus (HSV-1) immediate early protein ICP22 interacts with cellular proteins to inhibit host cell gene expression and promote viral gene expression. ICP22 inhibits phosphorylation of Ser2 of the RNA polymerase II (pol II) carboxyl-terminal domain (CTD) and productive elongation of pol II. Here we show that ICP22 affects elongation of pol II through both the early-elongation checkpoint and the poly(A)-associated elongation checkpoint on a protein-coding gene model. Coimmunoprecipitation assay… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…This study also demonstrated that the viral protein ICP27 coprecipitated with Spt5 in a DRB-responsive manner, while another group further identified ICP22 as a major determinant for Spt5 localization to viral DNA [42]. Spt5 is also copurified with ICP22 in HeLa nuclear extracts [43]. Affected by at least three viral proteins and remaining associated with transcribing polymerases after the pause release, Spt5 would thus be an interesting focus of future work.…”
Section: Promoter Clearance and Promoter-proximal Pausingmentioning
confidence: 58%
See 4 more Smart Citations
“…This study also demonstrated that the viral protein ICP27 coprecipitated with Spt5 in a DRB-responsive manner, while another group further identified ICP22 as a major determinant for Spt5 localization to viral DNA [42]. Spt5 is also copurified with ICP22 in HeLa nuclear extracts [43]. Affected by at least three viral proteins and remaining associated with transcribing polymerases after the pause release, Spt5 would thus be an interesting focus of future work.…”
Section: Promoter Clearance and Promoter-proximal Pausingmentioning
confidence: 58%
“…Interestingly, transiently expressed ICP22 was found on a cellular gene by ChIP, suggesting that the loss of CTD phosphorylation is not a result of failure to recruit CDK9 to sites of transcription [51]. Instead, ICP22 and CDK9 are recruited to sites of transcription, and at least for cellular genes, this leads to a local reduction in pS2 hyperphosphorylation and transcriptional elongation as measured by ChIP qPCR [43,51].…”
Section: Ctd Phosphorylationmentioning
confidence: 99%
See 3 more Smart Citations